Influence of Hypochlorous acid on Dimensional change, reproduction of details and compatibility with gypsum products of Addition Silicon Impression Material - 1) Mohammed J. Mohammed, (2) Shorouq M. Abass ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
Background: Patient saliva, plaque, or even blood can contaminate dental impressions. the disinfecting impression materials with disinfectants can help prevent contamination. However, these chemicals could alter the dimensional stability, reproduction of details and compatibility with gypsum products. Aim: This research aimed to showed how the dimensional change, reproduction of details and compatibility with gypsum products of the Addition Silicon impression material (PVS) affected after it was immersed in to two different disinfectants (5.25% sodium hypochlorite NaOCl for ten minutes and 200 ppm hypochlorous acid HOCL for 15 minutes). Methods: sixty PVS samples (Express STD, 3MESPE, USA). were splited into three test groups, each group of ten samples for each group test. The samples were prepared using a ring mould with the thirty mm diameter and a three mm wall thickness samples were immersion in two disinfection solutions: NaOCL at 5.25% and HOCL at 200 ppm. The group serving as the control received no disinfection. The dimensional change and compatibility with gypsum products of the samples was measured by using a digital microscope, while the reproduction of details was measured by inspected visually without magnification. Results: The dimensional change, reproduction of details and compatibility with gypsum products of the PVS non-significantly differ from those of a control group (P>0.05). Conclusion: Within a limitation of this study, PVS can be disinfected more effectively by being immersed in 200 ppm HOCL for 15 minutes while maintaining its dimensional stability, reproduce details, and compatibility with gypsum materials.